In vivo functional analysis of the human NF2 tumor suppressor gene in Drosophila. - Heather S Gavilan; Rima M Kulikauskas; David H Gutmann; Richard G Fehon (PLoS ONE, 2014)
The proper control of tissue growth is essential during normal development and an important problem in human disease. Merlin, the product of the Neurofibromatosis 2 tumor suppressor gene, has been extensively studied to understand its functions in growth control. Here we describe experiments in which we used Drosophila as an in vivo system to test the functions of the normal human NF2 gene products and patient-derived mutant alleles. Although the predominant NF2 gene isoform, isoform 1, could functionally replace the Drosophila Merlin gene, a second isoform with a distinct C-terminal tail could not. Immunofluorescence studies show that the two isoforms have distinct subcellular localizations when expressed in the polarized imaginal epithelium, and function in genetic rescue assays correlates with apical localization of the NF2 protein. Interestingly, we found that a patient-derived missense allele, NF2L64P, appears to be temperature sensitive. These studies highlight the utility of Drosophila for in vivo functional analysis of highly conserved human disease genes.